1998
DOI: 10.1094/cchem.1998.75.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Lysophosphatidylglyceryl‐Remazolbrilliant Blue (LPG‐RBB) from the Surface of Dyed Wheat Starch Granules

Abstract: Cereal Chem. 75(3):294-296Wheat starch granule surface was covalently stained with Remazolbrilliant blue-R dye (RBB) and then extracted with 1% SDS containing 1% 2-mercaptoethanol (2-ME) at room temperature for 14.5 hr. The extracted blue-staining material (A 650 ) separated into two fractions. Low molecular weight (LMW) material was further purified by Sephadex G-75 size-exclusion chromatography and thin-layer chromatography. Infrared and nuclear magnetic resonance ( 1 H-NMR and 13 C-NMR) spectroscopy indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Using NMR spectroscopy in surface material analysis of wheat starch, it was found that lysophosphatidylcholine (LPC) was the main surface component extracted by Me/SDS (Jimeno et al 2002). Seguchi and Kanenaga (1998) isolated other phospholipids, namely lysophosphatidylglycerol (LPG), from wheat starch by mechanical forces (ie., 45 min of stirring). The presence ofphospholipids such as LPC, LPG, and lysophosphatidylethanolamine have previously been reported in wheat starch (Morrison 1983); however, this author postulated that the phospholipids seem to be a template for the amylose helix structure and are therefore important in maintaining the internal structure of starch.…”
Section: Introductionmentioning
confidence: 99%
“…Using NMR spectroscopy in surface material analysis of wheat starch, it was found that lysophosphatidylcholine (LPC) was the main surface component extracted by Me/SDS (Jimeno et al 2002). Seguchi and Kanenaga (1998) isolated other phospholipids, namely lysophosphatidylglycerol (LPG), from wheat starch by mechanical forces (ie., 45 min of stirring). The presence ofphospholipids such as LPC, LPG, and lysophosphatidylethanolamine have previously been reported in wheat starch (Morrison 1983); however, this author postulated that the phospholipids seem to be a template for the amylose helix structure and are therefore important in maintaining the internal structure of starch.…”
Section: Introductionmentioning
confidence: 99%
“…LPC was the main compound of LMW material, which was removed from the surface of wheat starch after one fold extraction. In spite of clear signal peaks assigned to LPC, it was not possible to identify the LPG-RBB complex such as Seguchi and Kanenaga (1998) reported either in the 3.3-4.4 ppm range or in the aromatic region.…”
Section: Discussionmentioning
confidence: 98%
“…In any case we consider it of interest to comment that the assignment by Seguchi and Kanenaga (1998) is unusual because they assigned each aromatic carbon atom in a range of 2-4 ppm. This broad assignment may be explained by the fact that the RBB dye is not a single chemical species but rather a mixture of compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations